Proteases-From Basic Structure to Function to Drug Design as Targeted Therapy - Kwok, Hang Fai; Shaw, Christopher; Walker, Brian (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In the two last decades, proteases have constituted one of the primary and important targets in drug discovery. The U.S. FDA has approved more than 12 protease therapies in the last 10 years, and a number of next-generation or completely new proteases are under clinical development. Protease inhibition strategies are one of the fastest expanding areas in the field of of drugs that show considerable promise. This Special Issue will focus on the recent advances in the discovery and development of protease inhibitors, covering the synthesis of protease inhibitors, the design of new chemical entities acting as inhibitors of special/particular types of proteases, and their mode of actions (Frolova et al. 2020; Slapak et al. 2020; Künnapuu et al. 2021). In addition, the new applications of these interesting compounds/biomolecules and their limitations have been discussed and described (Wang et al. 2020; Bartošová-Sojková et al. 2021).